Synthesis, Vibrational Spectroscopic Investigation, Molecular Docking, Antibacterial and Antimicrobial Studies of a New Anthraquinone Derivative Compound - Çelik, Sefa; Vagifli, Fidan; AKYÜZ, SEVİM; Özkök, Funda; Özel, Ayşen E.; Dosler, Sibel; Onur, Nihal (Taylor & Francis Inc., 2022)
A new anthraquinone derivative, 1-(2,5-dimethylpiperazin-1-yl)anthracene-9,10-dione, was synthesized and characterized by Fourier Transform-Infrared, Raman and nuclear magnetic resonance analysis. The optimized molecular geometry was obtained using Density Functional Theory, B3LYP method with a 6-311++G(d,p) basis set. The fundamental vibrational wavenumbers, IR and Raman intensities were calculated for the optimized structure and simulated spectra were compared with the experimental vibrational spectra. The calculated highest occupied molecular orbital and lowest occupied molecular orbital energies indicated the presence of charge transfer within the molecule. The antibacterial activities of the new amino anthraquinone derivate against gram-positive and gram-negative bacteria were determined. Molecular docking simulations were performed with the new anthraquinone derivative and DNA to reveal its anticancer property. It was found that the anthraquinone derivate was bound to DNA with a high binding affinity (Delta G = -31.8 kJ/mol) and interacted with the DG10, DC11 and DG16 residues via the intermolecular hydrogen bonds. Moreover, to investigate the antiviral activity of the compound and to expose its action mechanism as an antiCOVID-19 agent, in silico molecular docking studies were performed on the Angiotensin-Converting Enzyme-2, and SARS-CoV-2 targets (holo and apo forms of main proteases M-pro and spike glycoprotein).
Keywords: Anthraquinone; DFT Calculations; Molecular Docking; Vibrational Analysis